2020
DOI: 10.11591/ijece.v10i5.pp4824-4834
|View full text |Cite
|
Sign up to set email alerts
|

A new dynamic speech encryption algorithm based on lorenz chaotic map over internet protocol

Abstract: This paper introduces a dynamic speech encryption algorithm based on Lorenz chaotic map over internet protocol to enhance the services of the real-time applications such as increases the security level and reduces latency. The proposed algorithm was divided into two processes: dynamic key generation process using 128-bit hash value to dynamically alter the initial secret keys, and encryption and decryption process using Lorenz system. In the proposed algorithm, the performance evaluation is carried out through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The average time delay in the proposed algorithm and some of the related algorithms such as AES was compared. The achieved results concluded that, the proposed algorithm was effectively secure in contradiction of several cryptanalysis attacks and has valuable cryptographic properties such as diffusion and confusion for good voice communication on the Internet [18]…”
Section: Related Workmentioning
confidence: 92%
“…The average time delay in the proposed algorithm and some of the related algorithms such as AES was compared. The achieved results concluded that, the proposed algorithm was effectively secure in contradiction of several cryptanalysis attacks and has valuable cryptographic properties such as diffusion and confusion for good voice communication on the Internet [18]…”
Section: Related Workmentioning
confidence: 92%
“…Second, as the initial conditions and control parameters, use plain text or the secret key(s). Finally, some chaotic systems iteration is applied to generate the cipher text [10], [18], [19].…”
Section: Chaos Theory For Cryptographymentioning
confidence: 99%
“…The confusion stage and the diffusion stage are the two most important stages in a chaosbased image cryptosystem. Figure 4 illustrates a typical architecture block diagram [1], [18].…”
Section: Chaotic Mapsmentioning
confidence: 99%
“…In this method, information is encrypted before being distributed over an insecure networks. With this capability, cryptography has a widely range of applications: securing content distribution systems [2], improving digital rights management systems [3]- [4], establishing speech encryption [5]- [6], tracing traitor in a content distribution system [7], solving security problem in mobile computing [8]- [9], and many more. The strength of cryptography protocols relies on the encryption-decryption keys management: how to protect the keys from disclose to unauthorized parties.…”
Section: Introductionmentioning
confidence: 99%